Mesoscale Features in the Global Geospace Response to the March 12, 2012 Storm - Adewuyi, Mayowa; Keesee, Amy M.; Nishimura, Yukitoshi; Gabrielse, Christine; Katus, Roxanne M. (Frontiers in Astronomy and Space Sciences, 2021)
The geospace response to coronal mass ejections includes phenomena across many regions, from reconnection at the dayside and magnetotail, through the inner magnetosphere, to the ionosphere, and even to the ground. Phenomena occurring in each region are often connected to each other through the magnetic field, but that field undergoes dynamic changes during storms and substorms. Improving our understanding of the geospace response to storms requires a global picture that enables us to observe all the regions simultaneously with both spatial and temporal resolution. Using the Energetic Neutral Atom (ENA) imager on the Two Wide-Angle Imaging Neutral-Atom Spectrometers (TWINS) mission, a temperature map can be calculated to provide a global view of the magnetotail. These maps are combined with in situ measurements at geosynchronous orbit from GOES 13 and 15, auroral images from all sky imagers (ASIs), and ground magnetometer measurements to examine the global geospace response of a coronal mass ejection (CME) driven event on March 12th, 2012. Mesoscale features in the magnetotail are observed throughout the interval, including prior to the storm commencement and during the main phase, which has implications for the dominant processes that lead to pressure buildup in the inner magnetosphere. Auroral enhancements that can be associated with these magnetotail features through magnetosphere-ionosphere coupling are observed to appear only after global reconfigurations of the magnetic field.